Contribution of Aeromagnetic Data to the Structural Discontinuities Identification of Black Volta Catchment Aquifer System in Côte d’Ivoire - Kouame, Armel Kouadio; Youan Ta, Marc; Akokponhoue, Bertrand Houngnigbo; De Lasme, Omer Zéphir; Kouamé, Loukou Nicolas (European Scientific Journal, ESJ, 2023)
This paper focuses on improving the structural knowledge of the fissured aquifers of the Black Volta catchment in Côte d’Ivoire based on the mapping of magnetic lineaments, which represent magnetic discontinuities such as magmatic body contacts or tectonic faults. Four filtering methods, pole reduction (equator), gradient (vertical and hori-zontal), upward extension, and angle tilt, were applied to the residual magnetic field map to extract magnetic discontinuities while using the Oasis Montaj (Geosoft) program. Euler deconvolution coupled with the analytical signal provided, in addition to the horizontal location of the magnetic contacts, is an indication of their depths. The resulting structural map contains 458 structures, with lengths ranging from 9.03 to 66.54 km. Three directions, NW-SE, E-W and NE-SW, were detected with a predominance of the NW-SE direction. Depths estimated by Euler solutions range from 6.8 to 2847 m. This map is consistent with many faults already recognised or assumed by traditional structural studies and tectonic events affecting the Ivorian basement. These results contribute significantly to the improvement of the structural map of the Black Volta Basin in Côte d’Ivoire. In addition to the major known tectonic faults, numerous lineaments, particularly those at depth, have been highlighted by the present study.